2015
DOI: 10.18637/jss.v065.i04
|View full text |Cite
|
Sign up to set email alerts
|

kmlandkml3d:RPackages to Cluster Longitudinal Data

Abstract: Longitudinal studies are essential tools in medical research. In these studies, variables are not restricted to single measurements but can be seen as variable-trajectories, either single or joint. Thus, an important question concerns the identification of homogeneous patient trajectories.kml and kml3d are R packages providing an implementation of k-means designed to work specifically on trajectories (kml) or on joint trajectories (kml3d). They provide various tools to work on longitudinal data: imputation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
156
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(164 citation statements)
references
References 60 publications
0
156
0
8
Order By: Relevance
“…This method used a hill-climbing algorithm jointly with expectation-maximization. The optimal number of clusters was chosen according to the Calinski-Harabatz criterion (Genolini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This method used a hill-climbing algorithm jointly with expectation-maximization. The optimal number of clusters was chosen according to the Calinski-Harabatz criterion (Genolini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it was observed that frost only occurred in areas on the bottom of valleys, and in particular those with slope values less than 10 (the uppermost extent of the most extreme frosts). Visual matchups were conducted by generating surface maps of frost risk (a binary no risk or high risk), exporting these as a .kml file (kml package in R; Genolini et al, 2015) to Google Earth Pro, and comparing the CAP predictions with existing vegetation boundaries evident in the imagery (Fig. 5).…”
Section: Cold Air Pooling Model Calibrationmentioning
confidence: 99%
“…Data cleaning, analyses, and figures were done in R (version 3.4.0; R Development Core Team) using several packages (Bates et al 2015;Genolini et al 2015;Hijmans 2016;Liaw and Wiener 2002;Pebesma 2018;van Buuren and Groothuis-Oudshoorn 2011;Wickham 2017;Wilke 2017). Figure 1 shows the spatial distribution of built-up trajectories.…”
Section: Analysesmentioning
confidence: 99%